Perlindungan Hak Warga Negara dalam Perspektif Al-Qur’an dan Konstitusi - Muhammad Amin; Maula Sari (TAFSE: Journal of Qur'anic Studies, 2023)
Protection of citizens rights is a very urgent issue in Islam. As a perfect religion, Islam accommodates the rights of every individual to be protected and respected so that no one can take them away. This paper discusses the protection of citizens' rights in the perspective of the Koran. This paper uses library research (liberary research) with a descriptive qualitative approach. The Qur'an mentions at least six rights of citizens that must be protected. These rights include: the right to live, the right to work, the right to education, the right to express opinions, the right to religion, the right to be independent, and the right to be treated equally in the eyes of the law, economy and socio-culture. Rules regarding the rights of citizens in Indonesia are regulated in the 1945 Constitution (UUD) and its derivatives. Protection of the rights of citizens is a form of the presence of the state in protecting and defending the rights of every citizen.Abstrak: Perlindungan hak warga negara merupakan isu yang sangat urgen dalam Islam. Sebagai agama yang sempurna, Islam mengakomodir hak setiap individu untuk dilindungi dan dihormati agar tidak dapat dirampas oleh siapapun. Tulisan ini membahas tentang perlindungan hak-hak warga negara dalam perspektif al-Qur’an. Tulisan ini menggunakan penelitian perpustakaan (library research) dengan pendekatan kualitatif deskriptif. Al-Qur’an menyebutkan minimal ada enam hak-hak warga negara yang wajib untuk dilindungi. Hak-hak tersebut antara lain: hak untuk hidup, hak mendapat pekerjaan, hak memperoleh pendidikan, hak untuk mengeluarkan pendapat, hak untuk beragama, hak untuk merdeka, dan hak untuk diperlakukan sama di mata hukum, ekonomi dan sosial budaya. Aturan mengenai hak-hak warga negara di Indonesia diatur di dalam Undang-Undang Dasar (UUD) tahun 1945 dan turunannya. Perlindungan terhadap hak-hak warga negara merupakan wujud dari kehadiran negara dalam melindungi dan membela hak setiap warganya.